The Use of Multimedia in the Learning of Religious and Moral Education in Primary Schools. - Mutathahirin, Mutathahirin; Rambe, Anggi Afrina; Susanti, Weti; Roza, Afrina (Khalaqa: Journal of Education and Learning, 2024)
The religious culture implemented in schools is an effort to shape the students' good habits So religious culture is essential to be applied in schools so that students have an Islamic soul and noble character. The objectives of this study are: 1) To find out the form of religious culture in SMA Negeri 1 Pacet and Diponegoro Islamic High School. This research method uses qualitative research with a descriptive qualitative approach with a multi-case design, and data collection techniques with observation, interviews, and documentation. The results of this study are the forms of religious culture in SMA Negeri 1 Pacet: 1) Islamic Clothing, 2) Cultural greetings, 3) Istighasah and prayer together, 4) Tilawah al-Qur'an, 5) Salat Duhur and Asr in congregation, 6) Kultum, 7) PHBI, 8) Pondok Ramadhan, 9) Tahlilan, 10) Yasinan, 11) Friday Prayers in Congregation, 12) Dluha Prayers, 13) Banjari. While the Religious Culture in Diponegoro Islamic High School are: 1) Islamic Clothing, 2) Salam culture, 3) Istighasah and prayer together, 4) Dluha Prayers, 5) Tahlilan, 6) Prayers and Asr Prayers, 7) Friday Prayers' at Jama'ah, 8) Banjari, 9) Friday Almsgiving, 10) Tilawah al-Qur'an, 11) Safari Friday, 12) PHBI, 13) Pondok Ramadhan, 14) Alms Sacrifice.